Bilateral Total Hip and Right Knee Arthroplasty in a Sickle Cell Disease Patient with Multiple Joint Osteonecrosis: A Case Report and Literature Review - Michael Ebiyon Ugbeye; Kehinde Adesola Alatishe; Chukwuebuka Okezie (Nigerian Postgraduate Medical Journal)
Sickle cell disease is an autosomal recessive genetic disorder with the underlying pathology, resulting in sickling of the red blood cells in deoxygenated conditions. Osteonecrosis is a common orthopaedic manifestation of sickle cell disease, and total joint arthroplasty is the preferred option in managing patients with advanced disease. This article describes bilateral total hip arthroplasty and right total knee arthroplasty (TKA) in a 41-year-old woman, a known haemoglobin SS (HBSS) patient who presented to the outpatient clinic of National Orthopaedic Hospital, Igbobi, Lagos, with recurrent bilateral hip and right knee pain of 10-year duration, with associated stiffness, valgus deformity in the knee and severe limitation of function. She had sequential bilateral total hip replacement and right TKA. She had significant improvement in function in the follow-up period. The effectiveness of total hip and knee arthroplasties in HBSS patients with osteonecrosis is well demonstrated in this article.